PENILAIAN PASIEN JAMKESMAS TERHADAP KUALITAS PELAYANAN PERAWAT DI RUANG SAKURA RSUD DR. R. SOSODORO DJATIKOESOEMO BOJONEGORO - AHMAD MAFTUKHIN, AHMAD MAFTUKHIN; AHMAD ROZIQ, AHMAD ROZIQ (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2012)
Community Health Insurance  is a social assistance program for health care for the poor and not able. Quality assessment by the patient and patient satisfaction ratings can be used as material for the improvement of health services, especially in community health insurance patients. Patient satisfaction can be a tool to predict patient compliance and treatment will relate to actions to return the next patient in therapy and even associated with improved health status of patients. The purpose of this study was to determine the patient's assessment of the quality of nurse Community Health Insurance service in hospitals Dr Sakura. R. Sosodoro Djatikoesoemo Bojonegoro.This study used a descriptive design with survey and population approaches 32, sample 32 respondents, sampling by incidental sampling. Research variables, namely patient assessment of quality of  nurses community health insurance services. Methods of data collection using questionnaires and data processing done by editing, coding, scoring, and tabulating the data analyzed using percentages.The results of this study is more than most of the respondents in the Room of Dr. Sakura Hospital. R. Sosodoro Djatikoesoemo Bojonegoro In 2011, with a satisfactory assessment of the quality of nursing care as much as 18 respondents (56.25%). Satisfaction is the feeling of someone in comparing the performance or results, it is expected that with the srandardized service of community health insurance with respect to the factors underlying the patient can give the user satisfaction.Key words: Community Health Insurance, Quality Service, Nurses.